Diversity and Abundance of Plankton From Peunaga, Cut Ujong Estuary, Meulaboh, West Aceh - Eka Lisdayanti; Eko Perbowo Dian Hermawan; Ananingtyas S Darmarini; Rahmawati Rahmawati; Nurul Najmi (Juvenil, 2024)
ABSTRACTThe research aims to determine the structure of the plankton community in the waters of Gampong Peunaga Cut Ujong, Meureubo, Meulaboh, West Aceh. The study was conducted in September 2023. The collection point consisted of 3 stations, and sampling was carried out at high tide with three repetitions. The filtering process uses a plankton net with a mesh size of 30 µm. Phytoplankton at the research location consists of five classes, namely Cyanophyceae, Euglenophyceae, Chlorophyceae, Bacillariophyceae, and Dinophyceae. Meanwhile, zooplankton consists of 7 groups consisting of Protozoa, Rotifera, Crustacea, Polychaeta, Gastropoda, Pelecypoda, and Nematoda. Phytoplankton has the highest percentage in the Bacillariophyceae class, reaching 71.7%, and the lowest 1% (Dinophyceae, Euglenophyceae, and Chlorophyceae). The abundance of phytoplankton at station three during the study ranged between 2,025,600 cells/m3 - 6,710,400 cells/m3 and zooplankton in the range of 23,400 ind/m3 - 33,480 ind/m3. The average diversity index (H') for phytoplankton was 1.04, the uniformity index (E) was 0.40, and the dominance index (C) was 0.50. Meanwhile, zooplankton has values H' (1.42), E (0.65), and D (0.36). To maintain the Peunaga estuary area as an ideal buffer area, it is recommended to regularly monitor the community structure of aquatic biota (plankton, benthos, and fish).Keywords: buffer ecosystem, community structure, dominance index, Navicula sp.